Sistem Aplikasi Perjalanan Dinas Pada Direktorat Pengelolaan Imunisasi Kemenkes RI Berbasis Web - Kholifah, Desiana Nur; Komarudin, Rachman; Darmawan, Stefanus (Bianglala Informatika, 2025)
Official travel is travel carried out by individuals or groups within the territory of the Republic of Indonesia or abroad on orders from authorized officials. An employee from a company goes on an official trip as an official work assignment sent by the company. Various types of documents must be prepared when going on an official trip, namely an Assignment Letter and an Official Travel Order. The Indonesian Ministry of Health, Directorate of Immunization Management, still uses a manual system in managing its data. In manual data management, errors in recording official travel and costs incurred for each official trip can be found, there are clashes in official travel schedules between one employee and another employee. For this reason, based on the existing problems, a system is needed that supports this process so that it becomes easy to manage. data management. This research method uses the Waterfall method, based on the existing problems a system is needed that supports the process, namely by creating a web-based official travel application system. Official travel data can be organized because the official travel process is computerized